Elapid Snake Venom Analyses Show the Specificity of the Peptide Composition at the Level of Genera Naja and Notechis - Munawar, Aisha; Trusch, Maria; Georgieva, Dessislava; Hildebrand, Diana; Kwiatkowski, Marcel; Behnken, Henning; Harder, Soenke; Arni, Raghuvir [UNESP]; Spencer, Patrick; Schlueter, Hartmut; Betzel, Christian (Mdpi Ag, 2014)
Elapid snake venom is a highly valuable, but till now mainly unexplored, source of pharmacologically important peptides. We analyzed the peptide fractions with molecular masses up to 10 kDa of two elapid snake venoms-that of the African cobra, N. m. mossambica (genus Naja), and the Peninsula tiger snake, N. scutatus, from Kangaroo Island (genus Notechis). A combination of chromatographic methods was used to isolate the peptides, which were characterized by combining complimentary mass spectrometric techniques. Comparative analysis of the peptide compositions of two venoms showed specificity at the genus level. Three-finger (3-F) cytotoxins, bradykinin-potentiating peptides (BPPs) and a bradykinin inhibitor were isolated from the Naja venom. 3-F neurotoxins, Kunitz/basic pancreatic trypsin inhibitor (BPTI)-type inhibitors and a natriuretic peptide were identified in the N. venom. The inhibiting activity of the peptides was confirmed in vitro with a selected array of proteases. Cytotoxin 1 (P01467) from the Naja venom might be involved in the disturbance of cellular processes by inhibiting the cell 20S-proteasome. A high degree of similarity between BPPs from elapid and viperid snake venoms was observed, suggesting that these molecules play a key role in snake venoms and also indicating that these peptides were recruited into the snake venom prior to the evolutionary divergence of the snakes.
Keywords: natriuretic peptides; Notechis scutatus from Kangaroo Island; Naja mossambica mossambica; Snake venom; pharmacologically active peptides; Bradykinin potentiating peptides; Kunitz-type inhibitor; neurotoxin; cytotoxin